(untitled) (Forum Penelitian Agro Ekonomi, 2024)
Successful development has been demonstrated by an increase in food production and food supply. But the success was not followed by a reduction in food insecurity. Number of food-insecure population is still large and likely to increase. Law 18/2012 on Food mandates establishment of an independent food security and sovereignty. The goal is to increase production and food self-sufficiency. It also aims to improve food diversity and to meet safety, quality, and requirement. Food security should also be competitive in both domestic and international markets. The challenge is to optimize food production resources, management of decentralization and global environment. It is necessary to accelerate food development through enhancing more distributed, diverse food production. It is also carried out through development of food and local food culture, food production system modernization, food trade management, and strengthening public food reserves.